2017
DOI: 10.1007/s12402-017-0241-x
|View full text |Cite
|
Sign up to set email alerts
|

ADHD symptoms in healthy adults are associated with stressful life events and negative memory bias

Abstract: Stressful life events, especially Childhood Trauma, predict ADHD symptoms. Childhood Trauma and negatively biased memory are risk factors for affective disorders. The association of life events and bias with ADHD symptoms may inform about the etiology of ADHD. Memory bias was tested using a computer task in N = 675 healthy adults. Life events and ADHD symptoms were assessed using questionnaires. The mediation of the association between life events and ADHD symptoms by memory bias was examined. We explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…Finally, in addition to these abnormalities in SWA, our results provide novel evidence of hyperactivity-like behavioral pathology as a direct result of developmental trauma, a behavior considered by some to be a symptom of ADHD 67 , especially when not expressed in a novel environment and limited to the home cage 68 . Future research should assess whether the sleep abnormalities identified here may be viable biomarkers, or even therapeutic targets, for ADHD-like behavioral pathology.…”
Section: Discussionmentioning
confidence: 58%
“…Finally, in addition to these abnormalities in SWA, our results provide novel evidence of hyperactivity-like behavioral pathology as a direct result of developmental trauma, a behavior considered by some to be a symptom of ADHD 67 , especially when not expressed in a novel environment and limited to the home cage 68 . Future research should assess whether the sleep abnormalities identified here may be viable biomarkers, or even therapeutic targets, for ADHD-like behavioral pathology.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, stressful life events, stress at work and home, alcohol dependence, and impulsivity explained 11%–13% of the relation between ADHD symptoms and problem gambling. Individuals with ADHD are more likely to be stressed, to experience stressful life events, and to display memory biases ( Vrijsen et al., 2017 ). Regarding problem gambling, several sources of stress (i.e., family problems, relationship difficulties, or financial worries) have been found to favor the risk of developing this addiction and to even play a role in the decision-making process ( Biback & Zack, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study included several mediating variables [marital status ( Botterill et al., 2016 ; Harpin, 2005 ), employment ( Feigelman et al., 1995 ; Harpin, 2005 ), smoking status ( McClernon & Kollins, 2008 ; Petry & Oncken, 2002 ), alcohol dependence ( del Pino-Gutiérrez et al., 2017 ; Wilens, 2004 ), drug use ( Wareham & Potenza, 2010 ; Wilens, 2004 ), IQ ( Biederman et al., 2012 ; Rai et al., 2014 ), common mental disorders (CMDs; depressive episode and/or anxiety disorders) ( Becker et al., 2015 ; Clarke, 2006 ; Davidsson et al., 2017 ), BPD traits ( Matthies & Philipsen, 2014 ; Oliva et al., 2017 ), perceived stress and the number of stressful life events ( Biback & Zack, 2015 ; Vrijsen et al., 2017 ), and impulsivity ( Hodgins & Holub, 2015 ; Miller et al., 2010 )], which may be associated with or be the consequence of ADHD, and also be the cause of gambling problems. Sociodemographic variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on adopted children indicated a link between early deprivation and ADHD symptoms (Roskam et al, 2014 ), and numbers of SLEs have been associated with ADHD symptoms in childhood with small to moderate effect sizes (Humphreys et al, 2019 ). For healthy adults, we also found SLEs to be positively correlated with ADHD scores (Vrijsen et al, 2018 ), and childhood trauma (emotional and/or physical neglect, physical and/or sexual abuse) have been associated with increased risk of ADHD symptom (Capusan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 68%